The legal capacity of the human being conceived and protection of unborn life. the proposal to amend article 1 of the Italian Civil Code in the new global abortion framework (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The essay critically examines the proposed amendment to article 1 of the Italian Civil Code aimed at recognising the legal capacity of the unborn child from the moment of conception.
Keywords: Life protection; abortion; unborn human being; unborn child; legal capacity